2016
DOI: 10.1016/j.pmedr.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of participation in a cardiometabolic health check among underserved groups

Abstract: Cardiometabolic diseases affect underserved groups disparately. Participation in health checks is also lower, widening health inequalities in society. Two-stage screening (non-invasive health risk assessment (HRA) and GP consultations for high-risk individuals) seems cost-effective, provided that drop-out rates are low in both steps. We aimed to explore the process of decision-making regarding HRA participation among underserved groups (45–70 y): native Dutch with a lower socioeconomic status (SES), Turkish, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…In light of this, efforts to improve the uptake and eliminate the differences we see between attenders and non-attenders should thus target people with low educational level as well as the unemployed. Studies from The Netherlands and Scotland suggest that a face-to-face community-based approach, engaging peers and community leaders in outreach work can increase the attendance at health checks in socially deprived settlements [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, efforts to improve the uptake and eliminate the differences we see between attenders and non-attenders should thus target people with low educational level as well as the unemployed. Studies from The Netherlands and Scotland suggest that a face-to-face community-based approach, engaging peers and community leaders in outreach work can increase the attendance at health checks in socially deprived settlements [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed heterogeneous results for extended educational material and public information campaigns [ 17 , 27 ]. The extended information letter that we used in our study was not personalised, a potentially stimulating factor that might be addressed more with a face-to-face reminder [ 5 , 9 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-responders are reported to be more often male, smoke more often and being of younger age [ 5 , 7 , 8 , 10 14 ]. A lower socio-economic status (SES) and a migrant status is also reported to be related to non-response [ 5 , 7 , 9 , 10 , 15 ]. If these groups could be reached with targeted response enhancing strategies, this could lead to an increased participation.…”
Section: Introductionmentioning
confidence: 99%
“…Deze combinatie van verhoogd risico en lagere deelname aan opsporingsiniatieven draagt bij aan het vergroten van de bestaande gezondheidsverschillen. Om meer inzicht te krijgen in de beweegredenen van kwetsbare groepen met betrekking tot deelname aan het PreventieConsult en hen te ondersteunen bij het maken van een geïnformeerde beslissing, voerden wij het CHECK'D-onderzoek uit [2]. Dit onderzoek bestond uit 21 focusgroepen en uit een interventie waarbij we een getrechterde uitnodigingsstrategie (schriftelijk → telefonisch → persoonlijk door de huisarts) testten.…”
Section: Check'd-onderzoekunclassified